2013
DOI: 10.1016/j.jbankfin.2012.12.007
|View full text |Cite
|
Sign up to set email alerts
|

The disposition effect and investor experience

Abstract: We examine whether investing experience can dampen the disposition effect, that is, the fact that investors seem to hold on to their losing stocks to a greater extent than they hold on to their winning stocks. To do so, we devise a computer program that simulates the stock market. We use the program in an experiment with two groups of subjects, namely experienced investors and undergraduate students (the inexperienced investors). As a control procedure, we consider random trade decisions made by robot subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
59
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(67 citation statements)
references
References 31 publications
(35 reference statements)
4
59
0
4
Order By: Relevance
“…The emergence of disposition effects is empirically (e.g., Odean, 1998;Dhar and Zhu, 2006) and experimentally (e.g., Weber and Camerer, 1998;Da Costa Jr et al, 2013) well-confirmed for single investors. Hence, we expect that single investors in our experiment will exhibit disposition effects.…”
Section: Hypotheses and Experimental Proceduresmentioning
confidence: 68%
See 3 more Smart Citations
“…The emergence of disposition effects is empirically (e.g., Odean, 1998;Dhar and Zhu, 2006) and experimentally (e.g., Weber and Camerer, 1998;Da Costa Jr et al, 2013) well-confirmed for single investors. Hence, we expect that single investors in our experiment will exhibit disposition effects.…”
Section: Hypotheses and Experimental Proceduresmentioning
confidence: 68%
“…Da Costa Jr et al (2013) argue that experienced traders exhibit smaller disposition effects than students. Moreover, disposition effects become smaller when the purchase prices of stocks are prominently displayed (Frydman and Rangel, 2014) or when automatic-selling options are used (Fischbacher et al, 2014).…”
Section: Experiments On the Disposition Effectmentioning
confidence: 99%
See 2 more Smart Citations
“…Those researchers observe that investors who gain more investment experience through frequent trading are less vulnerable to the disposition effect. In comparing experienced investors and undergraduates students, Costa et al (2013) find that both groups are subject to the disposition effect but that the experienced investors are less so. The relevance of price movements is indirectly observed by Weber and Camerer (1998).…”
Section: Drivers Of Investment Mistakesmentioning
confidence: 87%